Grade 1 Vertebral Fractures Identified by Densitometric Lateral Spine Imaging Predict Incident Major Osteoporotic Fracture Independently of Clinical Risk Factors and Bone Mineral Density in Older Women. (6th July 2020) - Johansson, Lisa; Sundh, Daniel; Magnusson, Per; Rukmangatharajan, Komagal; Mellström, Dan; Nilsson, Anna G; Lorentzon, Mattias
ABSTRACT: Because prevalent vertebral fracture (VF) is a strong predictor of future fractures, they are important to identify in clinical practice as osteoporosis medications are effective and can be used to reduce fracture risk in postmenopausal women with VF. Lateral spine imaging (LSI) with dual‐energy X‐ray absorptiometry (DXA) can be used to diagnose VFs accurately but is not widespread in clinical practice. The prognostic value of grade 1 (20% to 25% compression) VFs diagnosed by LSI with DXA has been insufficiently studied. The aim of this study was to determine if grade 1 VF is associated with incident fracture in older women. Sahlgrenska University Hospital Prospective Evaluation of Risk of Bone Fractures (SUPERB) is a population‐based study of 3028 older women from Gothenburg, Sweden. Included women were 75 to 80 years of age at baseline, answered questionnaires, and were scanned with DXA (Discovery A, Hologic, Waltham, MA, USA). LSI was used to diagnose VFs, which were classified using the Genant semiquantitative method. Cox regression models were used to estimate the association between VFs at baseline and X‐ray–verified incident fractures, with adjustment for confounders. Women with a grade 1 VF ( n = 264) or a grade 2–3 VF ( n = 349) were compared with women without any fracture ( n = 1482). During 3.6 years (median, interquartile range [IQR] 1.5 years) of follow‐up, 260 women had any incident fracture and 213 a major osteoporotic fracture (MOF). Women with only grade 1 VF had increased risk of any fracture (hazard ratio [HR] = 1.67; 95% confidence interval [CI] 1.18–2.36) and MOF (HR = 1.86; 95% CI 1.28–2.72). For MOF, this association remained after adjustment for clinical risk factors and femoral neck bone mineral density (BMD). In conclusion, grade 1 VFs were associated with incident MOF, also after adjustment for clinical risk factors and BMD, indicating that all VF identified by DXA should be considered in the evaluation of fracture risk in older women. © 2020 The Authors. Journal of Bone and Mineral Research published by American Society for Bone and Mineral Research..